Diel, seasonal and multiannual vertical zonation of copepod communities in the deep South Adriatic Sea under different environmental conditions - HURE, MARIJANA; BATISTIĆ, MIRNA; GARIĆ, RADE (Mediterranean Marine Science, 2025)
Abundance, diversity and vertical zonation of copepod communities were investigated in the oligotrophic southern Adriatic Sea (northeastern Mediterranean) over a broad time frame. A total of 136 depth-stratified samples (from the surface to 1200 m depth) were collected at day and night during nine cruises between June 2020 and September 2023. The highest copepod average abundance and diversity were found in the layers between 100 and 400 m depth during the day and in the upper 100 m depth at night, reflecting the patterns of diel vertical migration (DVM). Cluster analysis revealed three clearly defined groups of samples based on their depth range. Significant day – night differences were recorded in the epipelagic layer, which can be attributed to highly migratory species and the fine-scale vertical distribution of sub-surface (50-200 m) pelagic copepods. In contrast, diel and seasonal variations in the mesopelagic and deep zones were less pronounced. The vertical distribution of copepods in the upper layers correlated positively with temperature, salinity, and Chl a concentration. Periodic winter vertical mixing events disrupted the typical vertical structure, leading to the homogenization of the water column properties and the disappearance of the typical copepod community from the surface (0–50 m) both during the day and at night. These findings highlight the complexity of environmental processes in the southern Adriatic Sea and their role in shaping copepod community structure across spatial and temporal scales.